Do boicote à evangelização digital: a produção de sentido e a luta pelo reconhecimento nas interações comunicacionais acionadas por atores religiosos às telenovelas Babilônia e Apocalipse - Assunção, Évellin Aparecida Veras de (Universidade do Vale do Rio dos Sinos, 2020)
This research aims to investigate how the digital communicational interactions between social actors that mobilize the struggle for recognition (MARTÍN-BARBERO, 1997) in the religious boycotts of telenovelas, promoted by the Agente Gospel and FaceCatólico pages, affect the relationship between society and the television media in a mediatized environment. As a method, we used the reflection proposed by Ferreira (2012) on abduction, deduction, and induction, Braga (2008) and Marre (1991). Methodologically, we refer to Ferreira (2020), in his reflections on empirical research on circulation from the perspective of Verón and Levasseur (1989) and the case study (FRAGOSO; RECUERO; AMARAL, 2013). This perspective contributes to the analysis of the media process, especially to think about recognition through the circular movement of empirical research. Thus, we trace a relationship between the classic reception study with the study of the requirements that interact in networks and the maturity of a social response system (BRAGA, 2006; 2012), focusing on the accesses, uses, practices, and appropriations triggered by these we. In epistemological immersion, we seek to systematize perspectives visited bibliographically, as well as their questions and propositions, according to the empirical objects analyzed; conceptually delimit the main semantic operators mobilized; and relate these systematizations to the problem of mediatization, focusing especially on circulation (FERREIRA, 2016; 2020; GOMES, 2017a; FAUSTO, 2010). In comparing interactions based on religious boycotts, we identify modes of action, reaction, and the relationship between social actors and the media and infer about the construction of social and religious stigma in media circuits in digital networks.
Keywords: Boicote religioso; Luta pelo reconhecimento; Circulação; Interações comunicacionais; Evangelização digital; Religious boycott; Struggle for recognition; Circulation; Communicational interactions; Digital evangelization; ACCNPQ::Ciências Sociais Aplicadas::Comunicação